Academic performance in blended learning in higher education - Moreira, J. António (2014)
Institutions of Higher Education in Portugal face today unique challenges. Aware of the change, in general, these institutions have presented reform initiatives covering in their strategic plans new frames ofoperation, where e-learning and/or b-learning are recognized. The present study aims mainly to know the impact that b-learning and the implementation of some pedagogical models adapted to these environments may have on academic performance of students in higher education. Data analysis, referring to the classifications obtained, suggests that the creation of virtual environments, combined with complementary or face to face learning, and using pedagogical models adapted to online environments, diversified learning objects and strategies that encourage students, may indeed contribute to a significant improvement in their academic achievement. We also concluded that this b-learning modality, supported by online pedagogical constructivist and collaborative models allow effectively to equate the teaching learning process in a different way. This (new) reality implies a very significant cultural change, as it implies rethinking the roles of teacher and student, and the relationship between them, appropriate content, in addition to the implications that must be implemented in terms of structuring and planning courses and curricula, evaluation systems and teaching and learning forms.